Stress Response System in the Fish Skin—Welfare Measures Revisited - Kulczykowska, Ewa (Frontiers in Physiology, 2019)
The skin of vertebrates acts as a biological barrier defending the organism against many harmful environmental factors. It is well established that the main stress hormone cortisol, together with antioxidants such as melatonin (Mel) and its biologically active metabolites set up a local stress response system in the mammalian skin. Recently, our research group has shown that in fish there are basic conditions for the functioning of a cutaneous stress response system (CSRS) similar to that in mammals, where Mel with its biologically active metabolite AFMK (N1-acetyl-N2-formyl-5-methoxykynuramine) and cortisol act together to protect organism against unfavourable environment. Since aquaculture is making an increasing contribution to the global economy and new laws are demanding people to respect the welfare requirements of animals there has been increasing interest in indicators of fish well-being in aquaculture. This article addresses the problem of on-farm assessment of fish welfare and proposes the CSRS as a new source of information on the welfare status of farmed fish.